Analysis of the Need for Development of a Digital History Book of Dumai Port Based on Discovery Learning to Increase Historic Awareness of SMA Students at SMA Negeri Binaan Khusus and SMA Negeri 1 Dumai City - Margaretha Taniria Sarumaha; Sariyatun Sariyatun; Susanto Susanto (Budapest International Research and Critics University, 2022)
This study aims to analyze the needs of students and teachers for the development of digital teaching materials, namely the digital book of the history of the Dumai City port as local history and to see the level of historical awareness of high school students in Dumai City. This research is part of development research (R&D). This type of research is an expo facto research where researchers collect data systematically directly to respondents through data collection instruments. The process of collecting data is a very important stage in research. The data that has been collected will be used to test the hypotheses that have been proposed in the study where the data were obtained through interviews, observations and questionnaires. The data analysis technique was carried out in a quantitative descriptive manner. The results of the study show that (1) there is a positive view of the need for developing this digital book in the Specially Assisted State Senior High School and Dumai City 1 Public High School; (2) students' learning motivation is still relatively low for history subjects, this is due to the limited use of digital media used in the learning process; (3) history learning media is still very conventional; and (4) students' historical awareness of the existence of local history is still low.